Characterization of Fusarium species that affect the asparagus crops cultivation in Veracruz, Mexico - Sierra-Moya, Jennifer Andrea (2022)
Asparagus cultivation is highly profitable and is appreciated in international gourmet cuisine. In Mexico, the production of this vegetable is mainly for export, in the state of Veracruz it has been recently introduced. The objective of the research was to characterize by morphology, molecular techniques and pathogenicity test the Fusarium species isolated from symptomatic tissues of asparagus shoot. A directed sampling was carried out on plants that showed rot, wilting and dark brown spots. Fungal isolates were obtained from diseased shoots, which were disinfected and seeded on potato dextrose agar. Isolates were purified in monosporic cultures by hyphal tip. Four species of Fusarium were identified by taxonomic morphology, in a selective carnation leaf agar medium, then pathogenicity tests were carried out, complying with Koch's postulates. Next, the strains that were pathogenic were characterized by molecular techniques, and their identity as Fusarium oxysporum and Fusarium proliferatum was confirmed. The information obtained allows the implementation of appropriate management strategies for pathogenic species and thereby avoids economic losses in the short, medium, and long term in the asparagus crop.